2006
DOI: 10.1182/blood-2006-07-033597
|View full text |Cite
|
Sign up to set email alerts
|

Disease-associated mutations in CIAS1 induce cathepsin B–dependent rapid cell death of human THP-1 monocytic cells

Abstract: Mutations in the cold-induced autoinflammatory syndrome 1 (CIAS1) gene are associated with a spectrum of autoinflammatory diseases, including familial cold autoinflammatory syndrome, MuckleWells syndrome, and chronic infantile neurologic, cutaneous, articular syndrome, also known as neonatal-onset multisystem inflammatory disease. CIAS1 encodes cryopyrin, a protein that localizes to the cytosol and functions as pattern recognition receptor. Cryopyrin also participates in nuclear factor-B regulation and caspase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
93
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 96 publications
(103 citation statements)
references
References 62 publications
9
93
1
Order By: Relevance
“…LPS-treated monocytes expressing the Y570C mutation showed an increased necrotic-like cell death associated with lysosomal leakage and other cellular metabolic alterations. 80,81 Moreover, monocytes transfected with Y570C exhibited higher NF-kB activity compared to healthy controls. 82,83 A second important aspect is that some CINCA patients with milder symptoms apparently lack NLRP3 mutations but carry a latent lowlevel mosaicism.…”
Section: Genetics Of Inflammasomes In Autoinflammatory Diseasesmentioning
confidence: 98%
“…LPS-treated monocytes expressing the Y570C mutation showed an increased necrotic-like cell death associated with lysosomal leakage and other cellular metabolic alterations. 80,81 Moreover, monocytes transfected with Y570C exhibited higher NF-kB activity compared to healthy controls. 82,83 A second important aspect is that some CINCA patients with milder symptoms apparently lack NLRP3 mutations but carry a latent lowlevel mosaicism.…”
Section: Genetics Of Inflammasomes In Autoinflammatory Diseasesmentioning
confidence: 98%
“…Patient cells spontaneously released IL-1β in response to incubation at 32°C, a result that was blocked by anakinra, and that confirmed that modest cold exposure can trigger IL-1β release in these patients [21]. The role of mutant CIAS1-induced necrosis described in an in-vitro model needs further evaluation [22].…”
Section: Advances In Our Understanding Of the Pathophysiology Of Monomentioning
confidence: 99%
“…In the first report by Barton et al (1), the IVIG infusion was followed by a decrease in IgG and IgM serum levels within 72 hours, and a typical biopsy-proved cryoglobulinemic membranoproliferative glomerulonephritis. In a case described by Odum et al (2), IVIG infusion was followed within 48 hours by diffuse purpura, a rise in plasma creatinine levels, a microscopic hematuria, and high-level proteinuria strongly suggestive of glomerulonephritis. Yebra et al reported a flare of hepatitis C virus-related cryoglobulinemic vasculitis 4 hours after the first IVIG infusion, an increase of cryoglobulin precipitation, and depletion of the monoclonal IgM after in vitro addition of IVIG, and suggested that this simple method could help to predict the risk of cryoglobulin-IVIG immune complex formation and should be performed before starting IVIG in patients with mixed cryoglobulinemia (3).…”
mentioning
confidence: 98%